MUSIK DALAM PEMBELAJARAN ISLAM: SEBUAH TINJAUAN HISTORIS DAN KONTEMPORER - Muhamad Satria Wardana; Baharudin; Agus Susanti (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
Music has been used in Islamic education from classical times to the modern era for various purposes. However, there are differences in the views of scholars and changes in the method of their use as the times develop. This research aims to examine the use of music as a teaching tool in Islamic education in various historical periods, explore the views of scholars, and analyze the factors that influence the development of music in Islamic learning. This study uses a literature study method (library research) with content analysis techniques. The data sources consist of Islamic classical literature, journal articles, books, previous research results, and digital documents that discuss music in Islamic education. Source triangulation is done to ensure the validity of the data by comparing and confirming information from various references. The results of the study show that music has been used in Islamic education since the classical period to aid the learning of the Qur'an and Islamic science, as acknowledged by Al-Farabi and Al-Ghazali. In the Sufism tradition, music is a spiritual means and moral education. In the middle period, there was a difference of opinion on its use. In the modern era, technology expands access to music in education through digital media and interactive applications. Cultural acculturation also plays a role in its implementation, such as the use of gamelan in Java and gambus in Sumatra. Globalization has further encouraged the use of modern musical instruments in contemporary Islamic education. The results of this study provide insight into the dynamics of the use of music in Islamic education and its contribution to teaching methods. These findings can serve as a reference for educators and academics in developing innovative approaches that are in line with the times and still pay attention to Islamic values.